A Video Intervention to Increase Organ Donor Registration at the Department of Motorized Vehicles. Issue 4 (April 2020) - DuBay, Derek; Morinelli, Thomas; Redden, David; Rodrigue, James; Ivankova, Nataliya; Herbey, Ivan; Holt, Cheryl; Siminoff, Laura; Fouad, Mona; Su, Zemin; Martin, Michelle
Abstract : Background: The goal of this study was to increase organ donor registrations at the Department of Motorized Vehicles (DMV) via utilization of a sustainable, low-cost, African American-centric organ donation educational video. Results from previous studies provided a framework to generate a 10-minute video that featured registered organ donors, deceased donor families, and transplant recipients. Methods: The video was presented via an interrupted time series design (repeating on 2 mo, off 2 mo) on televisions placed in 6 regional DMVs. During the 12-month study, 162 387 patrons visited the DMVs. Results: Increases in organ donor registration were consistently observed in each DMV while the video was on compared with off (mean = +2.3% [range +1.98% to +3.35%]; P < 0.0001). Multivariable analysis demonstrated that females (odds ratio [OR], 1.29; 95% confidence interval [CI], 1.26-1.31), younger age (OR, 0.982/y; 95% CI, 0.982-0.983), and the video intervention (OR, 1.09; 95% CI, 1.07-1.12) were significantly associated with increased registration; while compared with Caucasian race, African American race was not (OR, 0.22; 95% CI, 0.22-0.23). There was no video-dependent effect on registration between Caucasians and African Americans ( P = 0.62). Exit interviews demonstrated only 16% of patrons could identify the key message in the video (becoming a registered organ donor). Conclusions: An educational video promoting organ donation resulted in increased organ donor registration at the DMV. The intervention was equally effective in African Americans and Caucasians. Future efforts should focus upon target-specific messaging and patron consumption of the educational video.